2020
DOI: 10.3389/fnins.2020.00306
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Auditory Task Components and of Their Relationships in Primate Auditory Cortex

Abstract: The current study aimed to resolve some of the inconsistencies in the literature on which mental processes affect auditory cortical activity. To this end, we studied auditory cortical firing in four monkeys with different experience while they were involved in six conditions with different arrangements of the task components sound, motor action, and water reward. Firing rates changed most strongly when a sound-only condition was compared to a condition in which sound was paired with water. Additional smaller c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…In the current study, we were able to use pupil size to explain changes in neural activity across both passive and active conditions. Changes in neural activity explained by pupil size are likely to overlap with some of the differences previously reported between task conditions, which may engage different levels of arousal (e.g., (Carcea et al, 2017;Knyazeva et al, 2020; Rodgers and DeWeese, 2014)). At the same time, pupil size is unlikely to explain changes in neural activity specific to a task.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In the current study, we were able to use pupil size to explain changes in neural activity across both passive and active conditions. Changes in neural activity explained by pupil size are likely to overlap with some of the differences previously reported between task conditions, which may engage different levels of arousal (e.g., (Carcea et al, 2017;Knyazeva et al, 2020; Rodgers and DeWeese, 2014)). At the same time, pupil size is unlikely to explain changes in neural activity specific to a task.…”
Section: Discussionmentioning
confidence: 88%
“…Several previous studies have shown that transitioning from passive listening to active behavior leads to sizable changes in neural activity in A1 (Fritz et al, 2003;Niwa et al, 2012;Otazu et al, 2009) and IC (Ryan and Miller, 1977;Slee and David, 2015). The specific changes depend on properties of the task stimuli (Fritz et al, 2003;Jaramillo and Zador, 2011;Lee and Middlebrooks, 2011) and on structural elements of the task, such as reward contingencies (David et al, 2012), task difficulty (Atiani et al, 2009), the degree of engagement (Carcea et al, 2017;Knyazeva et al, 2020), and the focus of selective attention (Hocherman et al, 1976;Lakatos et al, 2013;Schwartz and David, 2018). In the current study, we were able to use pupil size to explain changes in neural activity across both passive and active conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together it suggests that the strength and timing of the information transfer between AC and dlPFC can be flexibly allocated and is dependent on task demands. Lastly, comparison of the active and passive conditions highlights the sustained nonsensory motor/reward related activity in "primary" sensory cortex (AC) (Knyazeva, Selezneva et al 2020).…”
Section: Discussionmentioning
confidence: 99%